2014
DOI: 10.1111/ced.12505
|View full text |Cite
|
Sign up to set email alerts
|

Nonuraemic calciphylaxis: response to treatment with pamidronate and negative pressure therapy

Abstract: Calciphylaxis is a rare cause of skin ulcerations and necrosis in patients with both normal renal and parathyroid function. Although calciphylaxis appears to be on the increase, treatments are mainly empirical, especially for wound care. The lesions in calciphylaxis are typically very painful and carry a high risk of infection, with sepsis being the leading cause of death in this serious disease. We report two cases of nonuraemic calciphylaxis, which responded to treatment with pamidronate and wound management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Although wound care is emphasized in the literature as a crucial aspect of CUA treatment, controversy still remains regarding how wounds are best cared for and whether surgical debridement should be part of routine CUA care [ 25 ]. This controversy stems from the concern that aggressive debridement could cause local injury that could worsen CUA lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Although wound care is emphasized in the literature as a crucial aspect of CUA treatment, controversy still remains regarding how wounds are best cared for and whether surgical debridement should be part of routine CUA care [ 25 ]. This controversy stems from the concern that aggressive debridement could cause local injury that could worsen CUA lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This case represents NUC wounds that were successfully treated with pamidronate infusions. To our knowledge, only two other case series reported the successful treatment of NUC with pamidronate, which were performed in Europe . The first reported case was in Germany by Schliep et al; he was able to treat calciphylaxis of unknown origin with 6 pamidronate infusion and a repeated skin biopsy showed that the arterial calcification had vanished .…”
Section: Discussionmentioning
confidence: 99%
“…The second reported case was in France by Lorriaux et al In that case series, both patients were initially treated with sodium thiosulphate, but that was discontinued because of side effects. They were then started on pamidronate disodium 30 mg infusions every 2 weeks, and a marked improvement was noted after eight infusions …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations